New Gerbera Daisy Varieties for Large Containers and Flower Gardens - Zhanao Deng (EDIS)
Gerbera daisy is one of the most popular flowers in the United States. Recently, interest has increased in growing gerberas in large containers for indoor or outdoor use. ‘Funtastic™ Tangerine Eye’ and ‘Funtastic™ Golden Eye’ have been selected and tested specifically for use in large containers. These cultivars produce large, powdery mildew-resistant plants and large, attractive flowers in orange-red or yellow-orange that complement the existing Funtastic™ series of gerbera cultivars. This 8-page fact sheet was written by Zhanao Deng, and published by the UF Department of Environmental Horticulture, September 2013.